Application of quality-of-life measurements in clinical trials and in clinical practice for gynecologic cancer patients. (February 2010) - Greimel, Elfriede; Nordin, Andrew John
Gynecologic cancer teams care for women with malignancies of the ovaries, fallopian tubes, uterus, cervix, vagina and vulva. Gynecologic cancer therapies have become increasingly tailored to individual risk factors and are frequently multimodal. Clinical trials are necessary to assess the effectiveness of new treatment regimes, and measurement of differences in impact on quality of life (QoL) has become as important as assessment of disease-free and overall survival. Site-specific gynecologic cancer QoL measurement tools have been developed to improve the sensitivity of QoL assessment and to capture a broad range of issues relevant to each specific cancer and treatment modality. QoL assessment tools must be valid, reliable and sensitive to measure the differences in QoL domains in the populations in which they are used, and their development must be methodologically sound and transparent in order that researchers can have confidence that the instruments are fit for purpose. With improving survival rates for most gynecologic malignancies, survivorship issues are becoming increasingly important, relating to all domains of QoL. Patient-reported outcome measures are becoming integral components of cancer follow-up pathways and survivorship programs, identifying physical, psychological or functional legacies that impact on QoL during the months and years following the completion of cancer treatment. Late effects that impact on sexual functioning are becoming especially important for cancers with effective treatment regimes affecting younger women. The development of valid outcome measures for assessment of sexual function for gynecologic cancer patients is a priority.